2017
DOI: 10.3389/fmicb.2017.01649
|View full text |Cite
|
Sign up to set email alerts
|

The Microbial Community Dynamics during the Vitex Honey Ripening Process in the Honeycomb

Abstract: The bacterial and fungal communities of vitex honey were surveyed by sequencing the 16S rRNA gene and the internal transcribed spacer region of ribosomal DNA. Vitex honey samples were analyzed at different stage of ripening; the vitex flower was also analyzed, and the effect of the chemical composition in the experimental setup was assessed. The results confirmed the presence of dominant Bacillus spp. as the dominant bacterial in honey, and yeast related genera was the main fungal in the honey, respectively. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 42 publications
2
41
0
Order By: Relevance
“…Bacillus spp. were also the most prevalent and constituted more than 67% of bacteria isolated from honey in the study conducted by Wen et al [ 36 ]. Instead of underlining Bacillus strains as producers of antibiotics, bacteriocins, or antifungal compounds authors have also indicated B. anthracis and many B. cereus as toxin-producer strains.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus spp. were also the most prevalent and constituted more than 67% of bacteria isolated from honey in the study conducted by Wen et al [ 36 ]. Instead of underlining Bacillus strains as producers of antibiotics, bacteriocins, or antifungal compounds authors have also indicated B. anthracis and many B. cereus as toxin-producer strains.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these shared groups, such as the order Capnodiales, have established associations with insects like scale and aphids (Stephenson, 2012). Other shared taxa, such as genera Cryptococcus and Hannaella, have been previously associated with plants (Wen et al, 2017). The one unique group distinctive as an indicator of added Na gut fungal communities were members of the hyphomycete genus Cladosporium, which is categorized as an osmotolerant mold (Araújo et al, 2020) and are found in a wide range of environmental habitats, including hypersaline waters (Bensch et al, 2012).…”
Section: Fungal Communitiesmentioning
confidence: 99%
“…Recently, Bacillus spp. were also reported as the most frequently isolated bacteria in honey, making up 67% of total isolates [34].…”
Section: Distribution Of the Bacillus Species Isolated From Stinglessmentioning
confidence: 99%